Genomic Variation in Vitis Vinifera, from Extant to Contemporary Varieties - Zeki Kaya; Funda Özdemir Değirmenci; Sevgi Yorulmaz; Kıvılcım B. Vural; Christina Luke; Christopher H. Roosevelt; Mehmet Somel; David B. Neale (Plant Molecular Biology Reporter, 2025)

Quantifying the resistance of Australian wheat genotypes to Pratylenchus thornei based on a continuous metric from a factor analytic linear mixed model - Bethany Rognoni; Clayton R. Forknall; Steven Simpfendorfer; Richard Daniel; Luke Neale; Alison M. Kelly (Euphytica, 2024)
Genetic resistance to the parasitic root-lesion nematode, Pratylenchus thornei , is one of the main management strategies cereal growers can use to minimise the impact of nematodes on winter cereal cropping. Screening of genotypes in the presence of P. thornei populations must provide reliable resistance measures that are realised under field conditions. Adoption of the latest statistical methodologies can help to better differentiate between resistant and susceptible genotypes. In this study, post-harvest P. thornei population densities were measured from a collection of 17 field experiments, with varying starting P. thornei population densities, conducted between 2011 and 2018 in locations across the northern grain growing region of eastern Australia. The experiments primarily consisted of wheat genotypes. The post-harvest P. thornei population densities were analysed across multiple environments in a linear mixed model framework, with a factor analytic structure used to model genotype by environment (G $$×$$ × E) interaction effects exclusively for wheat genotypes. In general, genetic correlations between environments were found to be high, indicating limited G $$×$$ × E interaction for resistance to P. thornei . Post-processing of results using the factor analytic selection tools (FAST) method provided a measure of the overall performance for each wheat genotype, as well as a stability measure reflecting the consistency of the resistance status across environments. The FAST method quantified genotype resistance on a continuous scale, better reflecting the nature of genetic resistance based on a quantitative variable such as nematode population density, and provided a statistically robust and informative means of aiding selection decisions for resistance to P. thornei .